Equilibrio, termodinámica y modelos cinéticos en la adsorción de Rojo 40 sobre tuza de maíz (2015)
Adsorption is a widely used method for treatment of dissolved pollutants. Diverse agro-industrial wastes have been explored as potential adsorbents, showing high efficiency in the removal of dyes. To scale this process kinetic and equilibrium models for each pair adsorbate-adsorbent are required. In this work the equilibrium, kinetics and thermodynamic of the corn cob - red 40 system under batch system at pH 2.0 at temperatures of 25, 40 and 55 °C were evaluated. Langmuir, Freundlich and Temkin models were selected to represent the isotherms, while Lagergren, Ho and Elovich equations for kinetics of the process. Freundlich model provided the best fit to the isotherms, while the adsorption kinetics was best described by the Ho equation and the values for the Gibbs free energy and entropy indicated the spontaneity and feasibility of the process.